DICTIONARY OF DAILY LIFE IN BIBLICAL AND POST-BIBLICAL ANTIQUITY, VOLUME I: A–DA - C Stenschke (Acta Theologica)
Christoff Stenschke reviews a book from YAMAUCHI, E.M. & WILSON, M.R. (eds.). (Peabody: Hendrickson, 2014). Xxxvi + 400 pp., ISBN 978-1-61970-460-2.